Between agreements and disagreements. Use of the Pragmatic Sanction to avoid the abuse of unequal marriages in the province of Buenos Aires - Fuentes-Barragán, Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article deals with the repercussions produced by the implementation of the consecutive versions of the “Real Pragmática de Matrimonios” [Royal sanction for marriage] in the Vice-royalty of Río de la Plata and, more speciically, in the Province of Buenos Aires, since its irst American proclamation in 1778 until the dawn of emancipation. We will analyze both the role of parents, supported by the Crown to decide the matrimonial fate of their children, as well as the reaction of the latter, who saw their rights limited and had to disobey their parents in order to become responsible for their own lives. After analyzing documents from various kinds of Argentinian historical iles, relevant historiographical variations are obtained. Those variations are meaningful, as they help us to explore the fascinating reality typiied by prejudice, family interests and individual feelings in the late colonial period.